Presence of positive skin prick tests to inhalant allergens and markers of T2 inflammation in subjects with chronic spontaneous urticaria (CSU): a systematic literature review - Melanie Mitsui Wong (Allergy, Asthma & Clinical Immunology, 2020)
Abstract Background Current guidelines do not recommend performing aeroallergen skin prick testing (SPT) in chronic spontaneous urticaria (CSU). Objective The objective of this review was to investigate the presence of aeroallergen sensitization and markers of T2 inflammation in subjects with CSU. Methods Systematic literature reviews to identify all studies that evaluated the presence of T2 markers of allergic inflammation in CSU subjects were performed. Results In 16 studies that assessed the prevalence of positive SPT to multiple aeroallergens in CSU, 38.5% of CSU subjects had positive SPT. In three controlled studies, 34.2% of CSU subjects had positive SPT to multiple aeroallergens, compared to 13.6% of controls (p = 0.047). In 18 studies that assessed the prevalence of house dust mite (HDM) positive SPT in CSU, 27.5% of CSU subjects had positive SPT. In three controlled studies, 27.5% of CSU subjects had positive SPT to HDM, compared to 2.1% of controls (p = 0.047). Overall, CSU subjects were 3.1 times more likely to be aeroallergen-sensitized (95% CI 1.7–5.8, p = 0.0002) and 6.1 times more likely to be HDM-sensitized (95% CI 3.7–9.9, p < 0.00001) than controls. Mean total serum IgE (tIgE) levels were 238 kU/L and median tIgE levels were 164 kU/L, which was greater than the upper 90th percentile of normal (< 137 kU/L). Compared to healthy controls, CSU subjects were 6.5 times more likely to have IgG autoantibody against FcεR1α (p = 0.001), 2.4 times more likely to have IgG anti-IgE antibody (p = 0.03) and 5 times more likely to have anti-thyroid peroxidase (anti-TPO) antibody (p = 0.02). When corticosteroids were withheld for ≥ 28 days, mean blood eosinophil percentage was elevated at 5.9% (normal < 4%), but other studies reporting absolute count found the mean was in the normal range, 239 $$× 10^{6} /$$ × 10 6 / L (normal < 400 $$× 10^{6} /$$ × 10 6 / L). Conclusion Increased aeroallergen sensitization, tIgE, autoantibodies and blood eosinophil percentage in the CSU subjects indicates the possible importance of T2 inflammation in the pathogenesis of CSU. Further studies may be warranted to determine if specific allergen avoidance, desensitization or improvement in the mucosal allergic inflammation present in asthma and/or rhinitis has any benefit in the management of CSU.